2023
DOI: 10.3390/medicina59050883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an 8-Week Exercise Program on Physical, Emotional, and Mental Health in Saudi Adolescents: A Pilot Study

Abstract: Background and Objectives: Physical activity is essential for adolescents to maintain a healthy lifestyle. The aim of this study was to assess the influence of an 8-week exercise program and motivation on physical activity levels, self-motivation, and mental well-being of adolescents in Saudi Arabia. Moreover, the impact of virtual coaching on physical, emotional, and mental health after an eight-week exercise program was examined. Materials and Methods: Twenty-seven participants, 18 females (67%) and 9 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…64 Studies have shown that higher motivation to participate in physical activity is associated with higher scores on positive mental health indicators and lower scores on indicators of mental health problems, 65 and that eight weeks of physical activity can significantly improve adolescent mental health. 66 According to the World Health Organization, adolescents need 1 h of moderate-to-vigorous physical activity per day to promote their physical and mental health. A study on the relationship between physical activity and mental health showed that adolescents exercised 2.5-7.5 h per week to achieve the best mental health promotion benefits.…”
Section: Mental Health Mediates Between Physical Activity and Deviant...mentioning
confidence: 99%
“…64 Studies have shown that higher motivation to participate in physical activity is associated with higher scores on positive mental health indicators and lower scores on indicators of mental health problems, 65 and that eight weeks of physical activity can significantly improve adolescent mental health. 66 According to the World Health Organization, adolescents need 1 h of moderate-to-vigorous physical activity per day to promote their physical and mental health. A study on the relationship between physical activity and mental health showed that adolescents exercised 2.5-7.5 h per week to achieve the best mental health promotion benefits.…”
Section: Mental Health Mediates Between Physical Activity and Deviant...mentioning
confidence: 99%